A crystal plasticity model that accounts for grain size effects and slip system interactions on the deformation of austenitic stainless steels. (May 2022) - Agius, Dylan; Kareer, Anna; Mamun, Abdullah Al; Truman, Christopher; Collins, David M.; Mostafavi, Mahmoud; Knowles, David
Highlights: A new potential for modelling complex grain boundary interactions is presented. Includes a novel approach to introducing a grain size effect and slip transmission. Meso-scale simulations show a size dependence on predicted grain boundary stresses. Predicted plastic slip at grain boundaries was found to be misorientation dependant. Accurate macro-scale predictions of the Hall-Petch effect were also achieved. Abstract: To ensure a more representative simulation of meso‑scale and macro-scale deformation, it is important the underlying constitutive relations are advanced to more effectively incorporate the micro-mechanisms such as those operative near the grain boundaries. Critical features necessary for accurate predictions include the influence of grain size, morphology, and misorientation on the local deformation. In this study, a length scale dependence is incorporated into classical crystal plasticity simulations. The implementation is based on the influence of dislocation slip pile-up at grain boundaries based on the Hall-Petch theory in materials. This was achieved by applying a purpose-built algorithm to extract the slip distance in adjacent grains along each slip direction. This extracted data was used to adjust the critical resolved shear stress within the grain. The adjusted slip law was then implemented in constitutive models to predict the yield stress and hardening evolution of material for different grain sizes. The interaction of the slip systems between grains was also considered, which resulted in the adjustment in the extent of slip transfer permitted between grains based on misorientation. The proposed approach can be applied in both finite element and spectral methods for solving the continuum differential equations. The accuracy of the proposed model was investigated by considering the meso‑scale predictions using two-dimensional simulations, in addition to macro-scale predictions using three-dimensional models. Furthermore, the validity of the method was experimentally supported by tracking the development of intragranular residual elastic stresses, measured via high-resolution electron backscatter diffraction. The discussed results highlight a new potential of enhancing the way in which complex grain boundary interactions contribute to local deformation in crystal plasticity simulations.